The genus Neopseustis (Lepidoptera: Neopseustidae) from China, with description of one new species - Chen, Liusheng; Owada, Mamoru; Wang, Min; Long, Yang (Zootaxa, 2009)
The members of the genus Neopseustis Meyrick, 1909 from China are reviewed, and a key to the species is given. Neopseustis moxiensis Chen & Owada is described as a new species, characterized by the monotonous fuscous hindwings, and by the compressed clavate tegumenal lobes as well as slender uncinate apex of valvae. All the type specimens of new species are deposited in the Department of Entomology, South China Agricultural University, Guangzhou, China. Neopseustis fanjingshana Yang, 1988 (type locality: Guizhou) is redescribed on the basis of a male specimen, collected in Hunan. Diagnoses, notes and collecting data are given for N. bicornuta, N. sinensis, N. meyricki and N. archiphenax. A checklist of the Neopseustidae (4 genera, 13 species) is provided with their distribution.